A Class of 2-FP Codes. Issue 8 (17th November 2017) - Kathuria, Anu; Batra, Sudhir; Arora, S. K.
Abstract: In this paper we propose an explicit construction of a new class of binary 2-frameproof code of size 4(9+9n) and length 4(4+3n), n≥1. For this new class of 2-frameproof code, we show that the size of the code is almost three times the length of the code. By the definition of frameproof code in [2, 4] for a code C being 2-frameproof, minimum distance d of the code is given by, n is the length of the code. Moreover, as Plotkin Bound [18] relates the size of the code with minimum distance d and length of the code n for q = 2 defined as if . Here for this new class of binary 2-frameproof code, we show that the size of the code is large than the size of the code as obtained in Plotkin Bound[18].